Processos formativos paradoxais: a infância que equivoca e convida - Pereira, Júlia Flávia Gomes (2019)
This work is based on the experimentation of several research fields within the social assistance services of Grande Vitória (ES), the contact with childhood and its affectations regarding a process of formation of a psychologist. He speaks of experiences that, leaving the depths, increasingly gain the surface and allow paradoxes to appear and produce meanings, always double, and never unique. The analysis of the experiences finds passage in its multiplicity with the aid of Alice, personage of Lewis Carroll and of the logbooks written throughout this trajectory. The childhood that forges, that builds, that destroys, that mistakes and summons to thought.